Relationships between Fish Sizes and Otolith Sizes of Whiting (Merlangius merlangus Linnaeus, 1758) from the Western Black Sea - Taner Yıldız (Aquatic Sciences and Engineering)
The objective of this study was to determine the regressions between otolith sizes and shape indices vs. fish length, and weight of whiting, Merlangius merlangus (Linnaeus, 1758), from the Black Sea. Samples were collected randomly from commercial bottom trawlers between November 2017 and January 2018 in the western Black Sea. No differences were found in otolith size and indices by means of otolith position while a distinct difference by sexes was detected. Strong relations with high descriptive coefficients were found between otolith sizes and weight and fish length and weight. However, the regression relationships between otolith shape indices and fish length and weight were defined as very weak. As a conclusion, it can be emphasized that the otolith sizes and weight of whiting can be used for the determination of the size and weight of the fish.